GLOBALZATION AND RESULTING OPPORTUNITIES AND CHALLENGES FOR THE INDIAN PHARMACEUTICAL INDUSTRY - Arora, Gaurav (2009)
Indian Pharmaceutical industry in the past four decades has achieved a very good growth rate in the market. This has been made possible as a result of globalization which not only has made the industry very competitive but also offered many choices of products to the consumers in the market. At the same time globalization has resulted in many challenges as well as opportunities for the pharmaceutical industry and now the pharmaceutical industry has to improve its efficiency to maximize their potential in the market. This dissertation is an attempt to analyze the challenges and opportunities which have resulted for the pharmaceutical companies operating in the market as a result of globalization and has also recommended certain measures through which it can improve its potential in the market.